Penerapan Metode Focused Group Discussion (FGD) untuk Meningkatkan Kinerja Guru dalam Mengajar di MTs Nurul Ulum Tegalwangi Umbulsari Kabupaten Jember - Ghozali, Muhammad Yasin Yusuf (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
The purpose of this research can be formulated, namely to describe the application of the Focused Group Discussion (FGD) method to improve teacher performance in teaching at MTs Nurul Ulum Tegalwangi Umbulsari, Jember Regency. The approach used in this study is a quantitative approach, with the Action Research model. Research location is a place used in conducting research to obtain the desired data. This research took place at MTs Nurul Ulum Tegalwangi Umbulsari, Jember Regency, precisely on Jl. KH. Muh. Nur No. 01 Tegalwangi, Umbulsari District, Jember Regency. The time of the research is the time the research was conducted or when the research was conducted. This research was conducted on 01-30 August 2022. This madrasah action research was carried out by the Madrasa Supervisors with teachers at MTs Nurul Ulum Tegalwangi Umbulsari, Jember Regency. From the results of madrasah action research that has been carried out for two cycles and based on the discussion and analysis that has been carried out, it can be concluded that the application of the Focused Group Discussion (FGD) method can improve teacher performance in teaching at MTs Nurul Ulum Tegalwangi Umbulsari, Jember Regency. In the first cycle, the data obtained for the total value of 8.7, then an average of 1.74 (C) was obtained. Whereas in cycle II there was an increase in the total value of 13.7, an average of 2.74 (B) was obtained, which was a very good/good value.